Knowledge on Patient’s Rights among Nursing Students in a College of Pokhara - Shrestha, Prasamsha; Adhikari Baral, Mira (Journal of Nursing and Health Sciences Nepal, 2025)
Background: Patient’s rights are crucial for proper and ethical standard health care delivery in the health facilities. These rights are basic human rights that provide dignity, privacy, justice to patients and and protect them form maltreatment. Nursing students, who are future health care professionals have the responsibility of ensuring these rights. Nursing students are expected to experience ethically sensitive cases in their workplaces, and they should be well informed about patients’ right to provide ethically sound nursing care. This study aimed to assess knowledge of undergraduate nursing students on patient’s rights.Method: This was a descriptive cross-sectional study conducted on undergraduate nursing students of the School of Health and Allied Sciences, Pokhara University, located at Pokhara-30, Kaski. Data was collected using a structured self administered questionnaire developed by the researcher herself. A complete enumeration was done and data was collected from 128 respondents. Data were entered into SPSS version 22 and analysed using descriptive and inferential statistics. Chi-square test was used to determine the association between the level of knowledge on patient’s rights with selected background variables.Results: The study revealed that 44.5% of the respondents had Good Knowledge, 45.3% had moderate knowledge and 10.2% of the respondents had poor knowledge.Conclusion: Nearly half of the nursing students have good knowledge on patient rights. Age and educational programs influenced the level of knowledge of the students. Hence, there is a need for educational programs and a more focused curriculum to enhance students’ knowledge regarding patients’ rights.